Obstructive Sleep Apnea Syndrome: The Effect of Acute and Chronic Responses of Exercise - Stavrou, Vasileios T.; Astara, Kyriaki; Tourlakopoulos, Konstantinos N.; Papayianni, Eirini; Boutlas, Stylianos; Vavougios, George D.; Daniil, Zoe; Gourgoulianis, Konstantinos I. (Frontiers in Medicine, 2021)
Obstructive Sleep Apnea Syndrome (OSAS) is a sleep disorder with high prevalence in general population, but alarmingly low in clinicians’ differential diagnosis. We reviewed the literature on PubMed and Scopus from June 1980–2021 in order to describe the altered systematic pathophysiologic mechanisms in OSAS patients as well as to propose an exercise program for these patients. Exercise prevents a dysregulation of both daytime and nighttime cardiovascular autonomic function, reduces body weight, halts the onset and progress of insulin resistance, while it ameliorates excessive daytime sleepiness, cognitive decline, and mood disturbances, contributing to an overall greater sleep quality and quality of life.